Galicyjski Lwów "ocalony" w albumie Leszka Dulika i Waldemara Golca. Kresy w fotografii Henryka Poddębskiego (Rozważania lingwokulturologa) - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a linguocultural reflection on the correlation between image and word captured in an album monograph devoted to the borderlands, including the Galician borderlands, in the works of one of Poland`s most eminent photographers. This time its author focuses on the "linguistic data", which makes it possible to reconstruct the realities of Galician Lvov. The wide range of names included in the commentaries-descriptions of all the "Lvov" photographs in this proposal makes it possible to save people, places, objects, details, spaces, events from being forgotten.These have permanently become part of Galicia heritage, so strongly connected with its native history and cultural wealth.
Keywords: Lwów; Galicja; album; fotografia; werbalizacja; dane językowe; Lvov; Galicia; photography; verbalisation; linguistic data